(untitled) (Bangladesh Journal of Medical Science, 2024)
In countries like Morocco, drug-sensitive tuberculosis remains a major public health burden. Effective management of this condition is crucial, not only to achieve positive therapeutic outcomes for patients but also to curb its emergence and transmission. This study presents a detailed analysis of the therapeutic approach to drug-sensitive tuberculosis in Morocco. This retrospective study provides an overview of the therapeutic protocol used to treat drug-sensitive tuberculosis. The study examined all tuberculosis patients registered at the Tuberculosis and Respiratory Diseases Diagnostic Center in Kenitra from 2014 to 2017. A total of 5207 tuberculosis cases were recorded, with men comprising the majority of patients (63%) in this group, with a sex ratio of 1.7. The most affected age groups were 15 to 24 years and 25 to 34 years. Urban areas had a representation of 53%. The study revealed that 54% of cases were pulmonary, and extrapulmonary tuberculosis accounted for 46%. There were two main stages to the treatment regimens recommended by the WHO. During the initial phase, 96% of patients received a two-month quadritherapy (for new cases), 3% received a three-month regimen (for retreatment cases), and 2% received a three-drug therapy (for those under 15 years). This phase was followed by a continuation phase (bitherapy) lasting four to ten months. 82% of cases showed positive progression, 13% of patients experienced loss to follow-up, 1% had transfers out, and 2% of patients died. The study emphasizes the importance of integrating patient support, education on treatment, and the use of new technologies to enhance the monitoring and follow-up of tuberculosis patients. These measures could help reduce the morbidity and mortality associated with tuberculosis, contributing to overall health improvement. Bangladesh Journal of Medical Science Vol. 23 No. 02 April’24 Page : 521-526